Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/md.0000000000005875
|View full text |Cite
|
Sign up to set email alerts
|

Miliary tuberculosis

Abstract: The aim of this study was to determine the clinical features, and outcome of the patients with miliary tuberculosis (TB).We retrospectively evaluated 263 patients (142 male, 121 female, mean age: 44 years, range: 16–89 years) with miliary TB. Criteria for the diagnosis of miliary TB were at least one of the followings in the presence of clinical presentation suggestive of miliary TB such as prolonged fever, night sweats, anorexia, weight loss: radiologic criterion and pathological criterion and/or microbiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 44 publications
1
22
1
Order By: Relevance
“…A similar finding was demonstrated from Mert et al . [29] in Turkey in which 86% TB patients were anaemic. McDermid and colleagues [30] have reported that HB was significantly associated with TB even adjusting for TB susceptibility factors.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was demonstrated from Mert et al . [29] in Turkey in which 86% TB patients were anaemic. McDermid and colleagues [30] have reported that HB was significantly associated with TB even adjusting for TB susceptibility factors.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of other hematologic profiles, such as leukocytosis, thrombocytopenia and thrombocytosis, are reported to be approximately 10–20%. Increased alkaline phosphatase is a relatively common finding in a patient with TB, although the mechanism for this finding in TB is yet to be investigated [ 27 , 29 ]. Our study produced laboratory profiles of febrile EPTB similar to those of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, miliary TB can present as ARDS. It represents less than 8% of cases and it is associated with very high mortality (40–80%) despite mechanical ventilation and corticosteroids [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%